Pharmacokinetics of Cabotegravir in Subjects with Severe Renal Impairment. (4th October 2017) - Parasrampuria, Ridhi; Ford, Susan; Lou, Yu; Fu, Caifeng; Bakshi, Kalpana; Tenorio, Allan; Trezza, Christine; Spreen, William; Patel, Parul
Abstract: Background: Cabotegravir (CAB) is an integrase inhibitor in phase 3 clinical trials for the treatment and prevention of HIV. CAB undergoes glucuronidation via UGT1A1 with <1% renal elimination of unchanged CAB. Renal impairment may affect PK of drugs that are primarily metabolized or secreted in bile; thus impact of renal impairment on CAB pharmacokinetics was evaluated. Methods: This was a multi-center, single-dose study of oral CAB 30mg administered to subjects with severe renal impairment (creatinine clearance [CLcr] <30 mL/minute; not on renal replacement therapy) and to healthy controls (CLcr ≥90 mL/minute) matched for gender, age (±10 years), and body mass index (BMI) (±25%) (8 per group). Serial PK for plasma CAB concentrations were collected through 168 hours post dose and unbound CAB concentrations determined at 2 and 24 hours post dose. Non-compartmental PK analysis was performed; geometric least squares (GLS) mean ratios and 90% confidence intervals (CI) were generated. Results: Sixteen subjects completed study; 12 (75%) male, mean age 54 years (range:35–69), mean BMI 28 kg/m 2 (range: 24–35), and mean CLcr 22 mL/minute (range: 17–29) and 121 mL/minute (range: 95–162) for renal impaired and healthy subjects, respectively. CAB PK parameters were similar between severe renal impairment and healthy subjects. Based on preliminary PK, GLS mean ratios (90% CI) for AUC(0-¥), Cmax, C24, CL/F, and t1/2 were 0.97 (0.835, 1.14), 1.01 (0.865, 1.17), 1.02 (0.868, 1.20), 1.03 (0.881, 1.20) and 0.93 (0.831, 1.04), respectively. Although highly protein bound, the unbound fraction was higher in subjects with severe renal impairment with GLS mean ratio (90%CI) of 1.31 (0.843, 2.03) at 2 hours and 1.51 (1.19, 1.92) at 24 hours post dose. One renal impairment subject developed grade 3 lipase elevation considered drug-related by investigator, otherwise all reported adverse events (AE) were Grade 1 in severity with no serious AEs reported. Conclusion: Plasma CAB exposures in subjects with severe renal impairment were similar to healthy subjects; therefore, no dose adjustment of CAB is required in renal impairment. Although no data are available, CAB PK is not expected to be affected in subjects undergoing dialysis given CAB's non-renal clearance and high plasma protein binding ( 99%). Disclosures: R. Parasrampuria, GlaxoSmithKline: Employee and Shareholder, Salary; S. Ford, PAREXEL International: Employee, Salary; Y. Lou, PAREXEL International: Employee, Salary; C. Fu, PAREXEL International: Employee, Salary; K. Bakshi, GlaxoSmithKline: Employee and Shareholder, Salary; A. Tenorio, ViiV Healthcare: Employee and Shareholder, Salary; C. Trezza, ViiV Healthcare: Employee and Shareholder, Salary; W. Spreen, ViiV Healthcare: Employee and Shareholder, Salary; P. Patel, ViiV Healthcare: Employee and Shareholder, Salary